The Free Nutritious Meal (MBG) Program from the Perspective of Fiscal Policy - Risya Sandinata Putri; Yasira Faza; Siti Shabirah; Nasya Apritya Kuswanto; Zahra Syifa Dzakirah; Ahmad Setiawan Nuraya (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The Makan Bergizi Gratis (MBG) Program is one of the Indonesian government's priority policies aimed at improving the nutritional quality of the population while strengthening human resource development through food-based interventions financed by state expenditure. This study aims to analyze the MBG Program from the perspective of fiscal policy, particularly regarding its implications for the State Budget (APBN), socio-economic impacts, and the government's fiscal sustainability. The study employs a descriptive qualitative approach using a literature review method through the analysis of various scientific journals, regulations, government reports, and publications from relevant national and international institutions. The findings indicate that the MBG Program represents a form of expansionary fiscal policy that functions not only as an instrument of social protection but also as a long-term investment in human capital development. The implementation of this program has been shown to contribute to improving children's nutritional quality, reducing the risk of stunting, increasing educational participation and quality, and strengthening local economies through the involvement of food-based micro, small, and medium enterprises (MSMEs) and domestic supply chains. In addition, the MBG Program generates a multiplier effect on the economy through increased consumption, production, and employment absorption. However, the program also poses various fiscal risks, including increased pressure on the State Budget (APBN), potential budget inefficiency, and challenges related to the accurate targeting of beneficiaries. Therefore, the success of the MBG Program is highly dependent on effective governance, implementation efficiency, strengthened monitoring systems, and the government's ability to maintain a balance between social objectives and long-term fiscal sustainability.